2021
DOI: 10.3390/biom11121848
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Influence of Single-Site Mutations in the Central Cross-β Region of Amyloid β (1–40) Peptides

Abstract: Amyloid β (Aβ) is a peptide known to form amyloid fibrils in the brain of patients suffering from Alzheimer’s disease. A complete mechanistic understanding how Aβ peptides form neurotoxic assemblies and how they kill neurons has not yet been achieved. Previous analysis of various Aβ40 mutants could reveal the significant importance of the hydrophobic contact between the residues Phe19 and Leu34 for cell toxicity. For some mutations at Phe19, toxicity was completely abolished. In the current study, we assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To this end, several in vitro assays have been established: i) the classical 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) or (4-[3-(4-Iodophenyl)-2-(4-nitro-phenyl)-2H-5-tetrazolio]-1,3-benzene sulfonate) (WST-1) conversion assays representing the proportion of metabolically active cells, ii) the LDH release assay is indicative for plasma membrane disruption (dead cells), iii) caspase-3 staining which is used to investigate one of the possible pathways toward cell apoptosis, and iv) neurite length measurements to assess the effect of A𝛽 peptides on the outgrowth of neurites and thus information on the wellbeing under the applied conditions can be obtained. [84,[91][92][93]…”
Section: Methods In Amyloid Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, several in vitro assays have been established: i) the classical 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) or (4-[3-(4-Iodophenyl)-2-(4-nitro-phenyl)-2H-5-tetrazolio]-1,3-benzene sulfonate) (WST-1) conversion assays representing the proportion of metabolically active cells, ii) the LDH release assay is indicative for plasma membrane disruption (dead cells), iii) caspase-3 staining which is used to investigate one of the possible pathways toward cell apoptosis, and iv) neurite length measurements to assess the effect of A𝛽 peptides on the outgrowth of neurites and thus information on the wellbeing under the applied conditions can be obtained. [84,[91][92][93]…”
Section: Methods In Amyloid Researchmentioning
confidence: 99%
“…To this end, the positions F20 or G33 were mutated using a small library of four new mutants, namely, F20K , F20Y , F20Cha , and G33A . [ 91 ] The mutants F20K and F20Y showed a slightly shorter lag time, while F20Cha prolongs it. This could be attributed to the lack of a flat aromatic ring in the side chain at position 20, which might be important for the initiation of the fibril growth phase.…”
Section: Other Modifications Of the Aβ1−40 Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…(Kageyama et al, 2021). Aβ42 oligomers cause synaptotoxicity and memory loss (Fritzsch et al, 2021). It is therefore warranted to develop agents that can effectively inhibit the formation of Aβ oligomers or block their toxicity.…”
Section: Ad Inflammatory Mechanisms and Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Almost a year later Tycko et al showed that the hepta residue Aβ16-22: N-acetyl-Lys-Leu-Val-Phe-Phe-Ala-Glu-NH2, formed full length and highly ordered amyloid fibrils in vitro [155]. Substitutions for positions that stabilize the α-helical conformation (for instance, substituting Val18 by Ala) have been shown to reduce the amyloidogenic propensity of the peptides [156]. It is indeed intriguing that even single point substitutions can act as a veto against fibrillation.…”
Section: Sequence Requirementsmentioning
confidence: 99%